Isolation and Characterization of an Extracellular Polysaccharide from Physarum polycephalum - McCormick, J. Justin (1970)
The myxomycetes are called slime molds because of the synthesis of copious amounts of extracellular material (slime) during parts of the life cycle. In Physarum polycephalum, small amounts of slime are produced during exponential growth of microplasmodia in shake flasks, but the amount of this slime increased 10- to 20-fold at 16 to 34 hr after microplasmodia were induced to form spherules by transferring them to salt solution. The slime obtained during both periods is the same; an acidic polysaccharide consisting of galactose, sulfate, and trace amounts of rhamnose. Analysis of the galactose-to-sulfate ratio gave a value of about 4 to 1. Infrared spectroscopy showed increased absorbance at 820 cm(−1) characteristic of C-O-S vibrations. Electrophoresis on polyacrylamide gel revealed that the material moved as a single band which stained with Alcian Blue and periodic acid Shiff reagent. However, fractionation of identical material on Dowex columns and electrophoresis on cellulose acetate showed the slime to be made up of three major fractions. The polysaccharide appeared as an extracellular capsule closely adhering to the walls of the spherules. It could be separated from the wall by vigorous shaking. The increased synthesis of slime during spherulation was not blocked by cycloheximide, suggesting that new enzyme synthesis was not necessary for its formation.